2006
DOI: 10.3171/jns.2006.104.3.344
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ruptured intracranial aneurysms since the International Subarachnoid Aneurysm Trial: practice utilizing clip ligation and coil embolization as individual or complementary therapies

Abstract: Object. The aim of this study was to analyze the therapeutic decision-making process and outcome in 100 consecutive patients with aneurysmal subarachnoid hemorrhage (SAH) treated since the completion of the International Subarachnoid Aneurysm Trial (ISAT). All patients were evaluated and treated by a neurosurgeon with subspecialty training in both cerebrovascular and neuroendovascular surgery.Methods. One hundred consecutive patients with aneurysmal SAH who had been admitted within 1 week posthemorrhage and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 19 publications
0
18
0
3
Order By: Relevance
“…Moreover, as we have stressed in other publications, it is also important that the risk assessment is carried forward well into the procedure. 17 If, during coiling of a very small aneurysm, the procedure is judged to be technically more challenging than expected, we have a very low threshold to take the patient to surgery. Based on the morbidity and mortality rates observed in this meta-analysis among patients with very small unruptured aneurysms, endovascular treatment of these cases should be pursued very selectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as we have stressed in other publications, it is also important that the risk assessment is carried forward well into the procedure. 17 If, during coiling of a very small aneurysm, the procedure is judged to be technically more challenging than expected, we have a very low threshold to take the patient to surgery. Based on the morbidity and mortality rates observed in this meta-analysis among patients with very small unruptured aneurysms, endovascular treatment of these cases should be pursued very selectively.…”
Section: Discussionmentioning
confidence: 99%
“…La literatura indica que los aneurismas gigantes, con mala relación saco/cuello, fusiformes y de arteria cerebral media, no son buenos candidatos para tratamiento endovascular; sin embargo, el diseño de nuevos coils y técnicas como embolización asistida por balón o por stent y sole stenting; permiten obtener buenos resultados en los aneurismas mencionados. 5,[10][11][12][13][14][15] En este estudio se observó que todos los aneurismas gigantes, fusiformes, de arteria cerebral media, y 93 % (n=25) de los aneurismas de cuello ancho se embolizaron sin complicación, realizando embolización asistida con stent en dos casos y sole stenting en uno.…”
Section: Discussionunclassified
“…However, long-term follow up showed that endovascular occlusion of aneurysms is associated with a higher rate of regrowth and consecutive necessity of re-intervention [Molyneux et al 2009]. Nevertheless, numerous studies have been published with the aim of comparing surgical and endovascular aneurysm treatment in order to investigate the superiority of one over the other Therapeutic Advances in Neurological Disorders 4 (5) [Klompenhouwer et al 2011;de Oliveira et al 2007;Fraser et al 2006;Lanzino et al 2006;Taha et al 2006;Sandalcioglu et al 2005;van der Schaaf et al 2005;Hoh et al 2004;Wanke et al 2002].…”
Section: Treatment Modalities For Intracranial Aneurysmsmentioning
confidence: 99%